A qualitative study of 11 world-class team-sport athletes' experiences answering subjective questionnaires: A key ingredient for 'visible' health and performance monitoring? - McCall, A.; Wolfberg, A.; Ivarsson, A.; Dupont, G.; Larocque, A.; Bilsborough, J. (Sports Medicine, 2023)
Background: Athlete monitoring trends appear to be favouring objective over subjective measures. One reason of potentially several is that subjective monitoring affords athletes to give dishonest responses. Indeed, athletes have never been systematically researched to understand why they are honest or not. Objective: Because we do not know what motivates professional athletes to be honest or not when responding to subjective monitoring, our objective is to explore the motives for why the athlete may or may not respond honestly. Methods: A qualitative and phenomenological approach was used, interviewing 11 world-class team-sport athletes (five women, six men) about their experiences when asked to respond to subjective monitoring questionnaires. Interview transcripts were read in full and significant quotations/statements extracted. Meanings were formulated for each interviewees` story and assigned codes. Codes were reflected upon and labelled as categories, with similar categories grouped into an overall theme. Themes were examined, articulated, re-interpreted, re-formulated, and written as a thematic story, drawing on elements reported from different athletes creating a blended story, allowing readers a feel for what it is like to live the experience. Results: Overall, four key themes emerged: (i) pursuit of the ideal-self, (ii) individual barriers to athlete engagement, (iii) social facilitators to athlete engagement; and (iv) feeling compassion from performance staff. Conclusions: Our main insight is that athletes` emotions play a major role in whether they respond honestly or not, with these emotions being driven at least in part by the performance staff asking the questions.